A multidisciplinary care model to increase access to neurologic ambulatory care. Issue 3 (29th March 2021) - Hill, Chloe E.; Thomas, Bethany; Amendt, Alisha; Lawler, Meredith; Kalfin, Michael
ABSTRACT: Background: Expert patient care has been associated with improved outcomes for neurology patients, yet timely access to specialists is challenging. The employment of nurse practitioners (NPs) holds great potential to increase access to neurologic ambulatory care, however little practical guidance exists to date for how this may be achieved. Local problem: To improve timely care provision for patients with neurologic disease, we employed a multidisciplinary care utilization framework that used NPs to expand clinic appointment availability. Methods and intervention: After evaluating our baseline performance, we applied a standardized approach to the deployment of NPs in neurology clinic with regard to scheduling clinic sessions and patient appointments. The primary outcome measure was appointment availability measured over 6 months preintervention (June to November 2016) and 6 months postintervention (June to November 2017). Secondary measures included NP effort allocation. Results: The postintervention period demonstrated an increase in available appointments (3, 731 preintervention vs. 4, 318 postintervention) and scheduled appointments (2, 014 vs. 2, 685). Nurse practitioners spent more time practicing at the fullest extent of their licensure. All improvements were accomplished without the hiring of additional staff. Conclusions: A multidisciplinary care utilization framework for NP employment across neurology subspecialties resulted in an increase in appointment availability. Furthermore, this model is likely to be sustainable due to provider satisfaction and financial viability.